If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = 3 + -1(x + 6) Reorder the terms: 12 + 4x = 3 + -1(x + 6) Reorder the terms: 12 + 4x = 3 + -1(6 + x) 12 + 4x = 3 + (6 * -1 + x * -1) 12 + 4x = 3 + (-6 + -1x) Combine like terms: 3 + -6 = -3 12 + 4x = -3 + -1x Solving 12 + 4x = -3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 12 + 4x + x = -3 + -1x + x Combine like terms: 4x + x = 5x 12 + 5x = -3 + -1x + x Combine like terms: -1x + x = 0 12 + 5x = -3 + 0 12 + 5x = -3 Add '-12' to each side of the equation. 12 + -12 + 5x = -3 + -12 Combine like terms: 12 + -12 = 0 0 + 5x = -3 + -12 5x = -3 + -12 Combine like terms: -3 + -12 = -15 5x = -15 Divide each side by '5'. x = -3 Simplifying x = -3
| 27-3*2+8*4= | | 0.75(2)+0.25y=15 | | 4k-2=4k-8 | | 21x-13=10x+31 | | 0.75x+0.25y=15 | | 0.28m+0.1m=9.8 | | 0.75(2)+0.25(52)=15 | | 5(n+3)=2n-6 | | 50x(42-x)=1500 | | -6(x+1)=2(1-3x)-7 | | -3(x-9)=5 | | 3xy=P | | (6x^2+7x-3)=0 | | 5(x+.05)=-1.5(x+3x) | | -0.09(x-27)+0.03(x+3)=x+4 | | 5x-(3x-7)=4x-1(6x-35) | | k-4=5k-6k+14 | | a-1/3=2/3 | | (x+7)(2x-4)=0 | | -x/8=12 | | 5x/2-x=x/6-8/3 | | 9x+8-3x=3+5x+1 | | 3f=-21.6 | | 3(x+2)=5x-12 | | 4x-1=12x-17 | | 2(5-t)+6t=t+22 | | -7k+4-k=10k-2 | | -8/24= | | z+0.2=12.6 | | 5m+10=30 | | P-(P+15)=5(P-3)+3P | | 2x+3x-4=6 |